An Ontology for Property Crime based on Events from UFO-B Foundational Ontology - Mario de Oliveira Rodrigues, Cleyton; Luiz Gonçalves de Freitas, Frederico; Ribeiro de Azevedo, Ryan (BRACIS, 2016)
Property Crime has been highlighted as one of the major criminal offenses within the Brazilian Legal System. Moreover, it is common that there is some misunderstanding amongst the subtypes of this crime, such as Theft, Robbery, Misappropriation, and Extortion. We still emphasize the very nuance of legal literature that makes this domain as hostile as challenging: a weakly formalized knowledge, the presence of conflicts and ambiguities between norms, the heterogeneity of legal literature, as well as the diversity in reasoning models. Therefore, this article presents, inspired by UFO-B foundational ontology, a conceptual model for the representation of crimes against property in the Brazilian Criminal Code, in order to support some decision-making process, as the agents behavior classification and the inference of punishments. Thus, we present throughout this article, an ontological formalization for the Theory of Crime from Brazilian Penal Code, as well as for Property Crimes applications.